Exploring Differences Between Adolescents and Adults With Perinatal Depression—Data From the Expanding Care for Perinatal Women With Depression Trial in Nigeria - Oladeji, Bibilola D.; Bello, Toyin; Kola, Lola; Araya, Ricardo; Zelkowitz, Phyllis; Gureje, Oye (Frontiers in Psychiatry, 2019)
Background: Depression is common among women in the perinatal period. Although pregnancy and motherhood among adolescents are a global public health issue, little is known about how adolescents differ from adults in the occurrence and correlates of perinatal depression. Methods: Data was derived from a cluster randomized controlled trial of psychosocial interventions for perinatal depression in primary maternal care in Nigeria (the EXPONATE trial). Adolescents and adult participants recruited during pregnancy, and followed up till 6-months postpartum were compared on: proportions with depression (screening positive to depression on the Edinburgh Postnatal Depression Scale (EPDS) (score ≥12) and meeting the DSM-IV criteria using the short form of the Composite International Diagnostic Interview); adjustment and attitude to pregnancy and motherhood (using the Maternal Adjustment and Maternal Attitudes scale); and parenting skills (measured on Infant-Toddler version of the Home Inventory for Measurement of the Environment (HOME-IT)). Infant and fetal growth were assessed by measures of weight and head circumference at birth and upper mid-arm circumference (MUAC) at 6 months. Results: Of 8580 adults screened, 6.9% had major depression compared to 17.7% of 772 screened adolescents (p <0.001). Adolescents had significantly poorer adjustment and attitudes to pregnancy, lower mean fetal gestational age at birth and a smaller mean baby’s birth weight. At 6 months postpartum there were no significant differences in the rates of remission from depression between adolescent and adult women (EPDS score <6). Adolescent mothers continued to have poorer maternal attitudes and parenting skills indicated by significantly lower scores on the HOME-IT responsivity and involvement sub-scales. Infants of adolescent mothers had a higher rate of undernutrition (defined as MUAC <12.5cm) compared to those of adult mothers: 14.8% and 6.3% respectively (p=0.008), with the mean MUAC remaining significantly lower for infants of adolescent mothers after adjusting for their lower birthweight (p=0.04). Conclusion: Perinatal depression is more common and is associated with poorer maternal attitudes and parenting skills in adolescents compared to adults. Evidence from this exploratory study suggests that improving outcomes in infants of adolescent mothers with perinatal depression, depression treatment may need to be supplemented with specific approaches to improve parenting skills.